2019
DOI: 10.1186/s12879-019-4486-1
|View full text |Cite
|
Sign up to set email alerts
|

An updated systematic review and meta-analysis of the prevalence of hepatitis B virus in Ethiopia

Abstract: BackgroundHepatitis B virus is one of the major public health concerns globally. It is highly infectious and can be transmitted from person to person through vertically or horizontally via contaminated body fluids. Despite the provision of an effective vaccine, it remains a major problem worldwide, particularly among the developing countries.MethodsOnline electronic databases including PubMed, Google Scholar, Science Direct, African Index Medicus, African Journals Online, and WHO Afro Library were searched and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 99 publications
5
30
0
Order By: Relevance
“…In Ethiopia, even if there is lack of data representing the prevalence of hepatitis B infection nationally, according to the findings of some individual studies, the country is regarded as having a high burden of the disease. 18 As evidence, two recent systematic reviews and meta-analysis revealed that the overall prevalence of hepatitis B infection among the total population ranged from 6% to 7.4%, 19 , 20 while among pregnant women the range was 5% to7%, 20 , 21 a primary source of infection for the newborn. This finding is supported by a number of other studies conducted in the country, which found that the prevalence of hepatitis B infection among pregnant women ranged from 4.3% to7.9%.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, even if there is lack of data representing the prevalence of hepatitis B infection nationally, according to the findings of some individual studies, the country is regarded as having a high burden of the disease. 18 As evidence, two recent systematic reviews and meta-analysis revealed that the overall prevalence of hepatitis B infection among the total population ranged from 6% to 7.4%, 19 , 20 while among pregnant women the range was 5% to7%, 20 , 21 a primary source of infection for the newborn. This finding is supported by a number of other studies conducted in the country, which found that the prevalence of hepatitis B infection among pregnant women ranged from 4.3% to7.9%.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the prevalence of HBV ranged from 5% to 8% [ 11 ] in the Sub-Saharan region. Additionally, the estimated prevalence of hepatitis B virus (HBV) among the general population in Ethiopia was 6% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HBV infection among health workers ranges from 0.8% to 74.4%, although it depends upon the region where they work [ 11 ]. In Ethiopia, the pooled national prevalence of HBV among health care workers is estimated to be 5% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing vaccination coverage among healthcare works is vital in Ethiopia. The prevalence has shown progress from 7.4% to 6% with the current vaccination coverage 16 in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Health works are at high risk for viral infection compared to other ordinary people. Predisposing factors such as contamination due to medical procedures, workover load, and other factors are claimed to be responsible 10,11,14,16 . Moreover, regarding the accessibility of vaccines for health work remind a challenge particularly unavailability and cost are repotted 10,11,14 .…”
Section: Discussionmentioning
confidence: 99%